Erectile dysfunction in heart failure patients: a critical reappraisal. (22nd January 2013) - Alberti, L.; Torlasco, C.; Lauretta, L.; Loffi, M.; Maranta, F.; Salonia, A.; Margonato, A.; Montorsi, F.; Fragasso, G.
Summary Heart failure (HF) is a complex clinical syndrome with a constantly increasing incidence and prevalence in western countries. Total absence of sexual activity is registered in 30% of HF patients. Moreover, HF‐induced reduction in exercise tolerance, side effects of HF medications and the coexistence of shared risk factors between HF and sexual dysfunction may further aggravate the sexual health of HF patients. The purpose of this review is to examine the pathophysiological mechanisms behind the association of erectile dysfunction (ED) and HF, the potential therapeutic approaches and the eventual indications for sexual activity in HF patients. Medline and Cochrane Library search was performed from January 1970 through October 2012 to retrieve relevant papers outlining the association between ED and HF. Many evidences have outlined a tight association between ED and HF pathophysiological standpoint. Shared risk factors, common pathogenic traits and epidemiologic association represent some of the links between these conditions. Erectile dysfunction has been recognized as an earlier predictor of cardiovascular events; moreover, HF itself may cause and/or worsen ED because of its particular feature and co‐morbidities. Furthermore, some cardiovascular drugs may contribute to impaired erectile function. In stable patients with stable HF, sexual activity is generally not contraindicated but it should be encouraged, as a form of moderate‐intensity physical exertion. An effective treatment of ED in HF patients should be founded on the correction of reversible risk factors, on the choice of cardiovascular drugs with the lowest effect upon patient's erectile function, and on the use of phosphodiesterase‐5‐inhibitors. Physicians should be aware of the close relation between HF and ED and of the related clinical and therapeutic implications, in order to improve patients quality of life and clinical outcome.